The Val66Met brain-derived neurotrophic factor gene variant interacts with early pain exposure to predict cortisol dysregulation in 7-year-old children born very preterm: Implications for cognition. (7th February 2017) - Chau, C.M.Y.; Cepeda, I.L.; Devlin, A.M.; Weinberg, J.; Grunau, R.E.
Highlights: BDNF modulates the association between neonatal pain/stress & cortisol levels. ↑ pain/stress associated with ↓ hair, ↑ reactivity cortisol in boys with BDNF Met . Salivary cortisol reactivity −ve correlated with IQ & visual-motor integration. Met allele may increase vulnerability to neonatal pain/stress sex-dependently. Abstract: Early stress in the form of repetitive neonatal pain, in infants born very preterm, is associated with long-term dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis and with poorer cognitive performance. Brain-derived neurotrophic factor (BDNF) which is important in synaptic plasticity and cognitive functions is reduced by stress. Therefore the BDNF Val66Met variant, which affects secretion of BDNF, may interact with early exposure to pain-related stress in children born very preterm, to differentially affect HPA regulation that in turn may be associated with altered cognitive performance. The aims of this study were to investigate whether in children born very preterm, the BDNF Val66Met variant modulates the association between neonatal pain-related stress and cortisol levels at age 7 years, and if cortisol levels were related to cognitive function. Furthermore, we examined whether these relationships were sex-specific. Using a longitudinal cohort design, N  = 90 children born very preterm (24–32 weeks gestation) were followed from birth to age 7 years. Cortisol was assayed from hair as an index of cumulative stress and from saliva to measure reactivity to a cognitive challenge. BDNF Val66Met variant was genotyped at 7 years using real-time polymerase chain reaction (PCR). Using generalized linear modeling, in boys with the Met allele, greater neonatal pain-related stress (adjusted for clinical risk factors) predicted lower hair cortisol ( p  = 0.006) and higher reactivity salivary cortisol ( p  = 0.002). In both boys and girls with the Met allele, higher salivary cortisol reactivity was correlated with lower IQ ( r  = −0.60; p  = 0.001) and poorer visual-motor integration ( r  = −0.48; p  = 0.008). Our findings show associations between lower BDNF availability (presence of the Met allele) and vulnerability to neonatal pain/stress in boys, but not girls. This exploratory study suggests new directions for research into possible mechanisms underlying how neonatal pain/stress is related to cognitive performance in children born very preterm.